Divergence of RNA editing among Arabidopsis species. (March 2019) - Kawabe, Akira; Furihata, Hazuka Y.; Tsujino, Yudai; Kawanabe, Takahiro; Fujii, Sota; Yoshida, Takanori
Highlights: Detect 8 RNA editing changes in the chloroplast genome between Arabidopsis species. Both chloroplast genome and nuclear genome caused changes in RNA editing. An RNA editing change occurred by a deficiency in the PPR gene OTP80 . The changes in RNA editing occurred approximately every two million years and were not observed at functionally important sites. Abstract: RNA editing altered the RNA sequence by replacing the C nucleotide to U in the organellar genomes of plants. RNA editing status sometimes differed among distant species. The pattern of conservation and variation of RNA editing status made it possible to evaluate evolutionary mechanisms impacting functional aspects of RNA editing. In this study, divergence of RNA editing in the chloroplast genome among Arabidopsis species was analyzed to determine 9 losses and 1 gain in RNA editing. All changes in A. thaliana lineage resulted from changes to the chloroplast genome sequence, whereas changes in the A. lyrata / halleri lineage were possibly due to exclusive changes in the nuclear editing factors. One loss of RNA editing in A. lyrata was caused by a deficiency in the PPR gene OTP80 . The changes in RNA editing occurred approximately every two million years and were not observed at functionally important sites. These results highlight the conserved nature of RNA editing status suggesting the importance of RNA editing during evolution.